LITHUANIAN BOOKS IN THE COLLECTION OF THE DANISH PASTOR JOSIAS LORCK (1723–1785) - KLEIN, MANFRED (Knygotyra, 2011)
In the Kingdom of Denmark, as was the case in the rest of Europe, the 18th century was a period of bibliophilia and large private libraries. Josias Lorck (1723–1785), a protestant pastor in the German-speaking Frederick’s Church parish in Copenhagen who distinguished himself through his specialisation in Bibles in all the languages of the world, was one of the most outstanding collectors of his time. His collection, which at its peak counted over 5,000 different editions and at least as many etchings with biblical themes, was one of the Danish capital’s famous attractions even during his time. A catalogue of his collection, which was compiled posthumously in 1787, revealed that the collection also included some Lithuanian texts. According to the catalogue, there were six editions of the New Testament, the Psalms of David and the entire Holy Scripture which had been produced in Konigsberg between 1701 and 1755, partially as bilingual texts in German and Lithuanian.This article describes the formation of the collection and follows the complete Bible collection along its journey from Copenhagen to the possession of the State Library of Baden Wurttemberg in Stuttgart, Germany. Furthermore, the article provides a short description of the Lithuanian editions according to format/binding method, title, content and current condition, including any ownership marks. It seems Abstractthat Lorck personally marked his Bibles as his property. The question of the six Bibles’ origins is particularly interesting. The factors which are initially relevant are those regarding the identitiesof any intermediate owners and how the Bibles ultimately fell into the collector’s hands. Without the relevant ownership marks in the books, it is of course difficult to answer this question, especially given that Lorck’s writings contain very little information regarding the earlier Lithuanian Bibles that he acquired. This means that it is currently possible to establish reliably the previous owner of only one item. Probable previous owners of some other items have been identified by reference to an auction catalogue.Lorck acquired some 18th century Lithuanian texts on linguistics, perhaps in view of his Lithuanian Bibles, and possibly even along with them when they were purchased at auctions. After his death, these were sold at a series of three auctions along with the rest of his 20,000 book-strong library. Although Lorck’s Bibles bore an ownership mark, this was unfortunately not the case for all of his books. As a result, the location of these Lithuanian texts is currently unclear. The Royal Library of Copenhagen, which may directly or indirectly have acquired them, does not presently have a comprehensive overview of all the books from Lorck’s estate in their possession.
Keywords: ...